A systematic literature review of efficacy, effectiveness and safety of biologic therapies for treatment of familial Mediterranean fever. (13th June 2020) - Kuemmerle-Deschner, Jasmin B; Gautam, Raju; George, Aneesh T; Raza, Syed; Lomax, Kathleen G; Hur, Peter
Abstract: Objectives: To identify and summarize the existing evidence on the efficacy, effectiveness and safety of biologic therapies used, either as indicated or off-label, in the treatment of FMF. Methods: A systematic literature review was conducted using Embase ®, MEDLINE ®, MEDLINE ® -In Process, and Cochrane databases to identify randomized/non-randomized controlled trials (RCTs/non-RCTs) and real-world observational studies of FMF published as full-text articles (2000–September 2017) or conference abstracts (2014–September 2017). Studies with data for ≥1 biologic were included. Studies with <5 patients were excluded. Results: Of the 3342 retrieved records, 67 publications, yielding 38 unique studies, were included. All studies were published after the year 2010, and the majority (21) were full-text articles. Most studies (33/38) were prospective/retrospective observational; three were double-blind, placebo-controlled RCTs (one each of anakinra, canakinumab and rilonacept); and two were non-RCTs (both canakinumab). Anakinra (26), canakinumab (21) and etanercept (6) were the most frequently used biologics across studies, whereas use of adalimumab, tocilizumab, rilonacept and infliximab was limited (1–2 studies). The available evidence suggested benefits of anakinra and canakinumab in FMF. Conclusion: Anti-IL-1 therapies (i.e. anakinra and canakinumab) appear to be effective and safe options in the treatment of overall FMF, including patients with colchicine resistance and FMF-related amyloidosis. There is a need for properly designed prospective or controlled studies to conclude the superiority of one anti-IL-1 therapy over another. Evidence on the use of TNF-α and IL-6 inhibitors is limited, and further research is suggested.